New Habitat Data of the Green-Winged Orchid (Anacamptis Morio L.) Located in the Surroundings of Eger, Hungary: Further Data on this Protected Species of the Foothills of the Bükk Mountains - Misik, Tamás; Misik-Bartók, Dóra (Journal of Environmental Geography, 2023)
In 2022, we identified two new habitats of the protected green-winged orchid (Anacamptis morio L.) in the Bükk Mountains, in the surroundings of the city of Eger. One of the habitats is in the southwestern steppe meadow of the protected Nagy Eged Hill, while the other one is on a private plot near the village of Szarvaskő. A total of 18 blooming individuals were counted in the two sites. In the lower part of the steppe, at the foot of the protected Nagy-Eged Hill (47°97’56"N and 20°34’51"E), we found one well-developed green-winged orchid already in its flowering stage. It stood out with its smaller size and different flower colour from the lady orchids (Orchis purpurea HUDS.) widespread on the slopes of the mountain. Unfortunately, no other roots were found during our survey. The blooming flowers that make up the inflorescence were of the most common dark purple-red color. At the other site, further 17 individuals of the green-winged orchid were identified in a private garden (3,500 m2) in the outskirts of the village of Szarvaskő (47°92’02"N and 20°40’58"E). Most of the garden is covered by regularly mowed lawn. All of the detected orchids were in bloom and appeared scattered throughout the plot. Five larger plants grew at a great distance from one another, while 12 small ones (height: ≤10 cm) developed in a bunch. We had been aware of the presence of the protected orchid species on the plot since 2017, but before 2022 only a maximum of 3 flowering individuals appeared in one specific area of the plot each year. Floristic papers have not reported the occurrence of this species either in Nagy-Eged or in Szarvaskő so far.